LAW ENFORCEMENT OF THE BANDUNG REGIONAL REGULATIONS ON THE ORDERLINESS, CLEANLINESS, AND THE BEAUTY - Yesmil Anwar; Sigid Sigid Suseno; Nella Sumika Putri (Faculty of Law, Sriwijaya University, Indonesia, 2017)
The Number of sidewalk vendors in Bandung has reached 11,000 with no decline in growth according to the survey conducted by Indonesian University of Education/ Universitas Pendidikan Indonesia (UPI) in collaboration with Badan Perencanaan dan Pembangunan Daerah (Bappeda or regional development planning agency) Bandung. Sidewalk vendor is one of the main contributors to the dirtiness and traffic congestion in Bandung. Bandung has passed a Regional Regulation Numbered 3 and 5 about Cleanliness, Orderliness and the Beauty to prevent and to build the sidewalk vendors. However, lack of legal awareness and law enforcement may constrain the effectiveness of the regulation. Those regulations are particularly Bandung Regional Regulation Numbered 4/ 2011 concerning sidewalk vendors in which imposing high fine sanction not only for the seller but also for the buyer to prevent them from violating those regulations. To analyze the the compliance level of society and the effectiveness of fine sanction for the violation of regulations, this research used juridical normative approach and comparative method by comparing the regulation in Bandung with other Regional regulations related to sidewalk vendors in other cities in Indonesia such as in Surakarta and Surabaya. This research found that the law enforcement to the violation of sidewalk vendors regulation in Bandung city is not optimum due to lack of awareness to obey the law. The criminal sanction such as fine and forced fees are not able to prevent the violation of sidewalk vendors regulations. This research suggest that The Regional government of Bandung City: (1) needs to find a right model to keep sidewalk vendors in order by looking at the characteristics of the society and its social culture; (2) needs to search for a way to increase society’s compliance to any policies made by the government; and (3) needs to revise the current regulation